2015
DOI: 10.1186/s13104-015-1693-8
|View full text |Cite
|
Sign up to set email alerts
|

Placental site trophoblastic tumor and choriocarcinoma: an unusual presentation

Abstract: BackgroundMixed trophoblastic tumor composed of choriocarcinoma and placental site trophoblastic tumor was diagnosed on histopathology slides review, is a very rare mixed tumor and cured after adjuvant chemotherapy.Case presentationTwenty-nine years old, Para 2 female presented with 4 months history of irregular vaginal bleeding after an uncomplicated vaginal delivery. Abdominal examination showed 14 weeks uterus with β-hCG level of 14,889 mIU/ml. Slides review confirmed the diagnosis of placental site trophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Although ETT was recognized as a distinct GTN entity in 1998 by Shih and Kurman (2), ETTs combined with other gestational trophoblastic have been reported. MGTNs are extremely rare, and a review of English literature revealed that in addition to our case, there are 36 other MGTDs (Table 1) (2)(3)(4)6,(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 52%
“…Although ETT was recognized as a distinct GTN entity in 1998 by Shih and Kurman (2), ETTs combined with other gestational trophoblastic have been reported. MGTNs are extremely rare, and a review of English literature revealed that in addition to our case, there are 36 other MGTDs (Table 1) (2)(3)(4)6,(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 52%
“…Mixed GTNs are extremely rare, with only 20 mixed trophoblastic tumors having been reported [ 2 – 14 ], including our patient’s case. According to the literature, most mixed GTNs have occurred in patients of reproductive age (age range 15–60 years) and were usually associated with a previous gestational event [ 2 ].…”
Section: Discussionmentioning
confidence: 79%
“…27,28 During the course of many years and following intensive chemotherapy, there was recurrence as choriocarcinoma; we note that both of these forms of gestational trophoblastic neoplasia rarely develop simultaneously. 29 The lesson is that epithelioid trophoblast cells are easily misinterpreted as neoplastic squamous cells, a difficulty that was compounded in this case by the history of cervical squamous cell carcinoma, the older age of the patient, and the absence of known gestational trophoblastic disease. This is especially likely to be the case for trophoblastic neoplasms resembling the epithelioid trophoblastic tumor and the placental site trophoblastic tumor.…”
Section: Discussionmentioning
confidence: 87%